(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity, sedentary behaviour, and sleep (i.e. 24-hour movement behaviours) collectively impact health and wellbeing of older adults. The aim of this presentation is to present Slovenia’s first 24-Hour Movement Guidelines and adherence to those Guidelines among Slovenian older adults. Methods: The development process of the Guidelines followed the GRADE-ADOLOPMENT approach and was undertaken within the project “GIB24”, funded by the Slovenian Research and Innovation Agency and the Ministry of Health of the Republic of Slovenia. In 2024, the National Health-related Lifestyle Survey included a novel set of items that for the first time allow the assessment of adherence to the 24-Hour Movement Guidelines. A nationally representative sample of 17,000 Slovenian residents aged 18 to 74 years were invited to take part in the national survey. The invitations were sent via post to their home addresses, giving the participants an option to complete the survey in a paper-and-pencil format or online. Results: The Guideline Development Group identified the Canadian 24-Hour Movement Guidelines as the highest quality and decided to adopt most of their recommendations, supplementing them with additional best practice recommendations and a glossary. Preliminary findings from the National Health-related Lifestyle Survey 2024, based on responses from 1,461 adults aged 65 to 74 years (54.3% female), revealed that 40.2% adhered to the Combined 24-Hour Movement Guidelines (39.4% female, 41.0% male). Specifically, 74.6% reported accumulating at least 150 minutes/week of moderate- to vigorous-intensity physical activity, 87.9% reported spending no more than 7 hours/day engaged in sedentary behaviour, and 54.9% reported sleeping 7 to 8 hours/day. Notably, 2.2% of older adults did not meet any of the recommendations. Conclusions: The Guidelines present an important milestone in efforts to implement 24-hour movement behaviours as a determinant of healthy ageing in the Slovenian environment. Adherence to Guidelines among the Slovenian older adults could be considered as low, highlighting the need to strengthen the efforts that aim to promote healthy ageing among Slovenian older adults. Support/Funding Source: The authors gratefully acknowledge the Slovenian Research and Innovation Agency and Ministry of Health from the Republic of Slovenia for funding the project “Implementing the Concept of 24-Hour Movement Behaviours as a Determinant of Health Into the Slovenian Environment (GIB24)” (Project Number V3-2305). Keywords: Time-use epidemiology, recommendations, healthy ageing, GIB24, CINDI